HERODIETIC POTENTIAL OF FISH AND VEGETABLE PRODUCTS - Slashcheva, Alina; Moroz, Viktoriia (SWorld-Ger Conference proceedings, 2024)
The research is based on the idea of creating a puree semi-finished product made with Jerusalem artichoke, ginger and celery, which can act both as a filler and a functional ingredient (geroprotector) in the cutlet mass at the same time. The rational rati